Gender Based Financing Preferences of SMEs: Discouraged Borrowers - Singh, Richa (Université d'Ottawa / University of Ottawa, 2014)
The literature suggest that many young and small firms are discouraged borrowers, that is, they need finance but do not apply because they fear denial. This research aims to investigate demand-side financing differences between male and female-owned small and medium enterprises in Canada from the perspective of discouraged borrowers using secondary data from the "Survey on Financing of Small and Medium Enterprises, 2004" conducted by Statistics Canada. Women-owned firms are found to be credit constrained according to some studies, but not so in others. To date, however, there remain a lack of studies examining if there is a relationship between gender and discouragement. The study uses multivariate research methods to examine such a relationship while controlling for various firm-specific (age, size, industry, etc.) and owner-specific characteristics (experience). The study finds that majority-female owned firms are more likely to be discouraged borrowers as compared to majority-male owned firms. The study also offers support to arguments that relationship banking is important in reducing the probability of discouragement in both young and established firms.
Keywords: SMEs; gender; discouraged borrowers